The economy of early Greek colonisation in the northern Aegean - Gimatzidis, Stefanos (Journal of Greek Archaeology, 2020)
Greek colonisation has been one of the most popular topics in historical and archaeological debate already since the early modern period. Its study began in the historical context of early European colonialism, followed by rising liberalism during the early independence wars and French Revolution. It gained popularity after the industrial revolution in the Romantic period, when Greece and Rome were conceptualized as founders of Western culture and particularly in the age of New Imperialism that represented a new phase of colonial expansion faced with a growing awareness of social differences. Traditional perceptions of Greek colonisation were finally challenged during the most recent decolonisation period, particularly after the mid-20th century. All major historical events and intellectual movements of Modernity left their particular socio-cultural fingerprint on the studies of the Greek colonisation. One concept remained unchanged throughout this period. Greek colonisation was not fully emancipated – even in the decolonisation period – from preconceptions that emerged in the Zeitgeist of Western colonialism.